2015
DOI: 10.1371/journal.pone.0132134
|View full text |Cite
|
Sign up to set email alerts
|

EMX2 Is a Predictive Marker for Adjuvant Chemotherapy in Lung Squamous Cell Carcinomas

Abstract: BackgroundSquamous cell carcinomas (SCC) account for approximately 30% of non-small cell lung cancer (NSCLC). Current staging methods do not adequately predict outcome for this disease. EMX2 is a homeo-domain containing transcription factor known to regulate a key developmental pathway. This study assessed the significance of EMX2 as a prognostic and predictive marker for resectable lung SCC.MethodsTwo independent cohorts of patients with lung SCC undergoing surgical resection were studied. EMX2 protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…However, the migration capacity of H520 cells was restrained after upregulation of E-cadherin expression through CLDN3 overexpression, whereas the migration ability of SK-MES-1 cells was induced after downregulation of E-cadherin expression using CLDN3 shRNA transduction. Our current data were consistent with previous studies 38 , 39 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the migration capacity of H520 cells was restrained after upregulation of E-cadherin expression through CLDN3 overexpression, whereas the migration ability of SK-MES-1 cells was induced after downregulation of E-cadherin expression using CLDN3 shRNA transduction. Our current data were consistent with previous studies 38 , 39 .…”
Section: Discussionsupporting
confidence: 94%
“…Our own study also revealed that loss of E-cadherin expression was associated with the lymph node metastasis of lung SqCC and that loss of E-cadherin expression but increased β-catenin expression was associated with lung SqCC recurrence. Other previous studies of lung SqCC cell lines have shown that the migration ability of H2170 and H1703 cells was significantly upregulated after downregulation of E-cadherin expression 38 , 39 . In our current study, we found that reduced CLDN3 expression was associated with loss of E-cadherin expression in lung SqCC specimens but inversely associated with Vimentin expression, compared with the paired adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 60%
“…Adjuvant platinum-based chemotherapy remains the mainstay of treatment for non-small cell lung cancer. Though many predictive markers have been assessed 24 25 26 27 28 29 , no molecular marker has been shown to be useful for patient selection until recently. Besides the prognostic role, our present work also showed that high expression of KIAA1522 predicted poor responses for platinum-based chemotherapy, making it a potential biomarker of platinum-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…LADC cells commonly exhibit abnormal gene expression patterns and large numbers of gene mutations [ 2 ], and are characterized by specific biomarkers[ 3 7 ] and prognostic factors [ 8 10 ] that can be used to guide clinical diagnosis and treatment. LSCC cells also exhibit complex genomic alterations, including numerous gene mutations and copy number alterations [ 11 ], and are associated with particular biomarkers [ 12 14 ] and prognostic factors [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%